9. Etiology of bacterial community-acquired pneumonia among hospitalized children in Hai Phong Children’s Hospital - Anh, Dinh Duong Tung; Anh, Hoang Ngoc; Ly, Nguyen Khanh (Tạp chí Nghiên cứu Y học, 2023)
The objectives of this study were to determine the etiology of bacterial community-acquired pneumonia (CAP) in children hospitalized at Hai Phong Children’s Hospital (HCH) in 2019 and these bacteria’s antibiotic resistance properties. The subjects were the qualified medical records of all inpatients at the Respiratory Department of Hai Phong Children’s Hospital aging from 1 month to 15 years old diagnosed with CAP according to the diagnostic criteria of the World Health Organization with positive nasopharyngeal swab culture results from January 1st, 2019, to December 31st, 2019. The sample size included all medical records of patients who met the inclusion criteria of this research during the study period. The success rate of nasopharyngeal swab culture test of CAP patients was 638/1605 (39.7%). The most common pathogens of CAP in children at HCH were S. aureus, S. pneumoniae, H. influenzae and M. catarrhalis. Antibiogram revealed that each of them showed high resistance to a various type of antibiotics. Our study also provided valuable data on the antibiotic sensitivity and raised alarm over presence of multidrug-resistant bacteria inducing CAP in children.